Impact of implicit government guarantee on the credit spread of urban construction investment bonds - Rongda Chen; Han Li; Xuhui Tang; Chenglu Jin; Shuonan Zhang; Xinyu Zhang (Financial Innovation)
Abstract Financing sources for urban construction have garnered significant attention globally. Among various financing methods, the urban construction investment bond (UCIB) is unique to China. The UCIB credit spread, which represents the compensation for credit risk, has become a focal point for researchers. However, owing to shortcomings of previous approaches, few scholars have accurately assessed the impact of implicit government guarantees on credit spreads. This study introduces an innovative approach that uses orthogonal decomposition to extract proprietary information from credit ratings, reflecting implicit government guarantees. After accounting for bond factors, local government financing vehicle factors, and macroeconomic conditions, the implicit government guarantee substantially reduces the UCIB's credit spread. This conclusion remains robust when controlling for investor attention, regional factors, or duration.